DUNIA HITAM MADURA: GENEALOGI BAJING, ISLAM, DAN REZIM KESERAKAHAN - Ardhie Raditya (Universitas Merdeka Madiun, 2022)
Abstract: There is not much in-depth research on the black world of Madura. The study of the black world of Madura is still limited to West Madura, but ignores the side of East Madura. Unlike the black world in western Madura, actors in the black world of East Madura are often referred to by the terminology “Bajiman” or “Bajing Madura”. During this time, the black world of Madura has always been stigmatized by a dark world. Using an ethnographic postmodern approach shows data findings that the genealogy of the Madurese black world on the East Madura side is related to the people's struggle, traditional Islamic movements, and resistance strategies against the gluttonous regime. Based on the genealogy of the Madura black world on the East Madura side, it is confirmed that Bajing Madura contributed to the formation of Madura's progressive social history. Keywords: The Black World of Madura, Genealogy of Bajiman, Traditional Islamic Movements